Análise de Usabilidade do Geogebra para a aprendizagem de Geometria Espacial no Ensino Médio - Duarte, Carlos Eduardo Araújo (2018)
Spatial Geometry is the part of geometry that studies space, i.e., that studies shapes and objects in three dimensions. Studied primarily in high school, Spatial Geometry helps students in cognitive development by studying the mathematical content that is the closest to the real world. There are many software packages that help students to learn and, in Geometry, a world-wide known is the Geogebra, a software that aims to teach math for different levels of education, from basic to university. However, in order for a software to be used efficiently and effectively, according to ISO / IEC 9241-11, the system needs to compose usability characteristics. This work proposes a usability analysis of the Geogebra software in the teaching of Spatial Geometry using Usability Test with the participation of two groups of high school students, the first one of students who have used Geogebra and the second one of students who have never used the tool. Comparisons of the results of the tests were made using the time for completion of each proposed task and the post-test questionnaire, based on SUS( ​ System Usability Scale ​ ). With the collected data, it was observed that Geogebra has problems of interface and / or interaction with the user, presenting errors that led to a low score. In addition, some suggestions for improvements to the tool were included, based on the identified problems.